Developing an English Grammar Online Discussion Forum with Students as Contributors Using ADDIE Model - Kifli, Barli; Sinaga, Lidiman Sahat Martua; Pane, Isli Iriani Indiah; Siallagan, Lasenna (STKIP Singkawang, 2024)
This Research and Development (R&D) study addresses the issue of grammar proficiency among English Education students at Universitas Negeri Medan. The solution proposed is the development of a learning media in the form of a web-based English Grammar forum. The development involved the application of the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. This systematic framework led to the development of an innovative online discussion forum. In this forum, students take on the role of contributors, where they educate their peers on English grammar concepts, aligning with the